Smart Medication System For Elderly Person - Waheed, M. A; Pooja, P.G (International Journal of Computer Sciences and Engineering, 2025)
In present society, busy life has influenced individuals to overlook numerous things in everyday life. The elderly individuals need to take their medicines on time without missing. This project depends on IOT. The project is a smart medication system for elderly individual that reminds to take their solution. It additionally recognizes to the guardian whether medicine is taken or not. At a specific time set by the guardian through the application, the medication box reminds elderly by a sound yield. Moreover, to recognize the tablet to be taken at a specific time, LED lights will flicker in the right rack of medication box. These activities gets rehashed thrice a day i.e., morning, evening and night. The guardian gets notification from the application about the status of elderly that is whether elderly took medicine or not. The guardian can change the alert timings of pill box through the application. The guardian can likewise set the updates about any appointments of hospital which is appropriate for elderly. He can likewise observe the medicine history of elderly in the application.